Minat baca dan dimensi resiliensi anak berhadapan dengan hukum: Studi kasus LPKA kelas II Bandung - Barkatun Nisa Alfia; Khaerudin Kurniawan; Sumiyadi Sumiyadi; Vismaia S. Damaianti; Yeti Mulyati; Yulianeta Yulianeta (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to analyze the reading interests of Children In Conflict with the Law (CICL) and interpret them as indicators of mental resilience using the “I Have”, “I Am”, and “I Can” framework. This study uses a mixed-methods approach to examine the social phenomena experienced by children in conflict with the law, with 84 respondents. Data collection was conducted through structured questionnaires, in-depth interviews, observations, and documentation studies, which were then analyzed using thematic analysis. The results show the “I Have” framework as external support, with high scores across Compliance, Social, and Recognition. The “I Am” framework, as internal strength, includes aspects of Values and Curiosity, which also obtained high scores. Meanwhile, the “I Can” framework, as an interpersonal skills framework, contains aspects of Competition, Engagement, and Challenge, each with varying scores. These findings suggest that literacy programs in LPKA should be designed with a more holistic approach that not only meets CICL’s external needs but also stimulates their intrinsic motivation by selecting reading materials relevant to their cognitive and social development.